Novi sistem za upravljanje premostitvenih objektov v upravljanju DARS - Kušar, Matej (Gradbeni vestnik, 2021)
In developed countries, the trend in road infrastructure is shifting from construction to maintenance management. Road infrastructure consists of various components, with bridges being one of the most critical. It is therefore of great importance to the road network that their safety and serviceability are at least adequate. In Slovenia, bridge performance assessment has been based on the same methodology for almost 30 years. At the time of its development, it was comparable to the methodologies of other developed countries, but in the following decades it has not been significantly updated. After a three-year development, a completely new Bridge management system is put into use. To determine the bridge condition, several Key performance indicators are used: traffic safety, reliability, availability and economic efficiency. The decision optimization process is based on Incremental benefit cost analysis using heuristic optimization method.
Keywords: bridges; investicijsko vzdrževanje; maintenance; management; mostovi; upravljanje